Drawing and Dialogue: Youth’s Experiences With the “Face” of Diabetes - Shari K Liesch APNP, RN, CDE; Kathleen M Elertson DNP, APNP, CPNP-PC, FNP-BC, RN (Journal of Patient Experience, 2020)
Objective: The purpose of this qualitative pilot study was to evaluate drawing, narration, color use, and meaning through discussion to increase insight surrounding youth’s lived experience with type 1 diabetes. Methods: This qualitative study reflects a convenience sample of 20 (female = 12, male = 8) youth aged 8 to 15 years with an established diagnosis of type 1 diabetes. During a nonclinic session, 3 drawings—self-portrait, face of diabetes, and future self-portrait—were created. Interviews were completed with an art therapist or clinic nurse practitioner using a standardized script. Results: All “face” of diabetes drawings depicted images separate from self. The most frequent color noted was gray, due to pencil use. No significant difference in disclosures or dialogue were observed between interviews conducted by the art therapist or nurse practitioner. Emerging themes noted: diabetes is unpredictable and stigmatizing, causes fears, and impacts daily life, yet discussions evidenced overall coping and resilience. Conclusions: Drawing during clinic visits enhances communication and understanding of youth’s lived experience. Findings offer clinical benefit when managing care and support for chronic health conditions.